El perifiton como indicador decontaminación difusa: el caso de la cuenca superior del río Reconquista (Buenos Aires, Argentina) - Vilches, Carolina (2016)
Periphyton as indicator of non-point pollution: the case of upper basin of the Reconquista river (Buenos Aires, Argentina). Periphyton in the upper basin of the Reconquista River was studied in order to identify the species that compose and analyze possible changes in its structure due to diffuse pollution from agricultural activities. Six samplings were carried out between December 2006 and May 2008 at intervals of three months in eight reaches adjacent to areas where agricultural and cattle farming activities are developed. Significant differences between the two types of activity were found applying similarity analysis between communities being higher the concentration of chlorophyll-a and lower the autotrophy indexes in agricultural areas. A total of 158 species per reach were found with highly variable species richness (at least 10 species and 67 species maximum). Neither an outstanding dominance by any of the species nor among diversity estimated by Shannon index were found at all sites. The conclusion was that the presence of Ulnaria ulna and Gomphonema parvulum was associated with agricultural sites whereas Nitzschia palea, Raphidiopsis mediterranea and Trachelomonas sp3 were associated with cattle farming.